Strategic Management of a Company’s Employer Brand: Experience of International Companies (Marketing i Menedžment Innovacij)
This article examines the strategic management of employer branding in multinational companies and its significantly positive impact on talent acquisition and retention. In today’s competitive global marketplace, a robust employer brand is essential for organisations aiming to distinguish themselves and retain top talent. The concepts of employer brand development, talent acquisition, and employee loyalty assessment are challenging to monitor in the current domestic business environment. This raises the question of how companies with successful employer brands have developed their strategies and continue to sustain them in the marketplace. Therefore, the aim of this study is to develop strategic directions for the formation of the employer brand and its further alignment on the basis of the synthesis of successful practices from international technology companies. The employer brand diagnostic procedure includes three steps. The first step includes a general analysis of the employer brand of companies, such as the international companies Apple, Google and Microsoft, and a research roadmap of the mission and goals of the employer brand of international companies. The second step is to monitor the components of the employer’s internal and external brand. The third step is to assess employee loyalty with eNPS. It is argued that organisations should integrate the mission, vision and objectives of their employer brand and HR strategy with the overall mission, vision and strategy of the company. This alignment is critical to developing a cohesive corporate culture and, as a result, developing a clear employer brand value proposition. Managing employee loyalty is a critical aspect of employer brand monitoring, as it is necessary to maintain a positive work environment and establish effective external communication to nurture employer brand ambassadors. The developed strategic directions, which are based on the positive practices of international companies with developed employer brands, have practical applications for companies that want to manage the value proposition of their employees and align their employer brand identities.